Resin cross-linked shaped carbon fiber conductive base paper for hydrogen fuel cell and preparation process of resin cross-linked shaped carbon fiber conductive base paper
By using a combination process of asphalt-based carbon fiber, aramid pulp and low-concentration phenolic resin on carbon fiber base paper, the problem of difficulty in taking into account the breathability and conductivity of traditional carbon fiber base paper was successfully solved, and carbon fiber conductive base paper with high breathability and high conductivity was prepared, which is suitable for gas diffusion layer of hydrogen fuel cells.
Patent Information
- Application Number
- CN202510304674.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-14
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-03-14
AI Technical Summary
Traditional carbon fiber raw paper is difficult to accurately control during the resin reinforcement process, resulting in difficulty in taking into account both breathability and conductivity.
Asphalt-based carbon fiber is used as the skeleton and aramid pulp as auxiliary forming fibers. Through low-concentration phenolic resin impregnation and high-temperature carbonization, resin cross-linked fixed carbon fiber conductive base paper for hydrogen fuel cell is prepared.
It achieves a balance between high breathability and high conductivity, solves the contradiction between conductivity and breathability of carbon fiber paper, and improves the performance of the gas diffusion layer of hydrogen fuel cell.
Smart Images

Figure CN119900195A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the cross-technical field of special papermaking and carbon fiber material preparation, and specifically relates to a resin cross-linked and shaped carbon fiber conductive base paper for hydrogen fuel cells and a preparation process thereof. Background Art
[0002] As an efficient and clean energy conversion technology, hydrogen fuel cells directly convert the chemical energy of hydrogen and oxygen into electrical energy through electrochemical reactions. They have significant advantages such as high energy conversion efficiency, no pollution, and quiet operation. Its working principle is based on the reverse reaction of water electrolysis. At the anode, hydrogen is oxidized into hydrogen ions and electrons; at the cathode, oxygen reacts with hydrogen ions and electrons to generate water, completing the conversion of electrical energy. Hydrogen fuel cells have broad application prospects in transportation, distributed power generation, energy storage and other fields. For example, hydrogen fuel cell vehicles have become an important direction for the development of future vehicles due to their fast filling and long driving range. Its key components include proton exchange membranes, catalysts, gas diffusion layers and bipolar plates. The gas diffusion layer plays an important role in supporting the catalytic layer, conducting gas, and discharging reaction products in fuel cells. It is also an important carrier for current collection. However, due to the chemical corrosion in the working environment and high performance requirements, there are not many materials suitable for the gas diffusion layer of fuel cells. Carbon paper is a material that has been successfully commercialized by international companies such as Toray of Japan and SGL of Germany, and has extremely high commercial potential and value.
[0003] Carbon paper is made from carbon fiber paper through processes such as carbonization, graphitization, and hydrophobic treatment. The structure and performance of carbon fiber paper determine the quality of the final carbon paper. However, carbon fiber itself has the characteristics of strong interfacial inertness and high brittleness, making it difficult to prepare carbon fiber paper with high conductivity and high air permeability.
[0004] In order to obtain carbon fiber base paper with high air permeability, scientific and technological workers have successively used polyethanol, phenolic resin and other glued carbon fibers, and then cured them at high temperature to obtain carbon fiber base paper. For example, US20180069245 used 15% polyvinyl alcohol to glue carbon fibers and successfully prepared flexible carbon fiber paper. CN202411510294.2 prepared carbon fiber paper for fuel cell gas diffusion layer by resin impregnation, hot pressing and graphitization. US2006214320 obtained carbon paper with a deflection of 1.5 to 4.8 mm by mixing with cellulose and impregnating with phenolic resin. In addition, CN102465475A mixed polyacrylonitrile-based carbon fibers with serpentine cotton wool, and successfully prepared industrial high-temperature carbon fiber electric heating paper by wet papermaking process, but these methods still have problems of insufficient air permeability or introduction of impurities. Summary of the invention
[0005] Aiming at the problem that the resin strengthening process of traditional carbon fiber base paper is difficult to accurately control, resulting in difficulty in taking both air permeability and electrical conductivity into consideration, the present invention provides a resin cross-linked and shaped carbon fiber conductive base paper for hydrogen fuel cells and a preparation process thereof, wherein asphalt-based carbon fiber is used as a skeleton and aramid pulp is used as an auxiliary forming fiber, and low-concentration phenolic resin impregnation and high-temperature carbonization are used as reinforcement to prepare carbon fiber conductive paper, so as to solve the contradiction between the electrical conductivity and air permeability of carbon fiber paper.
[0006] The present invention is achieved through the following technical solutions: A process for preparing resin cross-linked and shaped carbon fiber conductive base paper for hydrogen fuel cells comprises the following steps: S1, shredding aramid pulp and soaking it in deionized water to obtain aramid pulp soaking liquid A, then adding PEO dispersant to obtain a mixed system B; S2, adding carbon fiber to the mixed system B for re-dispersion, and obtaining carbon fiber paper E through wet forming; S3, immersing the carbon fiber paper E in the phenolic resin dispersion F, and then drying and hot pressing to obtain the carbon fiber paper H; S4, carbonizing the carbon fiber paper H under oxygen-isolating conditions to obtain a carbon fiber conductive base paper.
[0007] Preferably, the relevant requirements of aramid pulp are as follows: length is 3-8 mm, diameter is 7-8 μm, resistivity is 1.5-2.0 μΩ·m, tensile strength is 2.2-2.4 Gpa, and elongation at break is 0.25%-0.26%; The concentration of the PEO dispersion is 5-6 g / L; the conductivity of the deionized water is (0.08-0.1) μS / cm.
[0008] Preferably, in S1, the ratio of aramid pulp B to water is 1.0-1.2 g: 2 L, and the aramid pulp soaking time is more than (6-8) h; The amount of the PEO dispersant used is (1.5-2.0) wt% of the total absolute dry mass of the carbon fiber and aramid pulp, and the number of revolutions during disintegration is (10000-20000) rpm.
[0009] Preferably, the preparation method of carbon fiber paper E is: S21, adding asphalt-based carbon fiber to the mixed system B, mixing evenly and dispersing again to obtain a mixed fiber slurry C; S22, homogenizing and dehydrating the mixed fiber slurry C to obtain a wet paper web D; S23, the wet paper web D is subjected to vacuum drying to obtain carbon fiber paper E.
[0010] Preferably, in S21, the absolute dry weight ratio of the added asphalt-based carbon fiber to the aramid pulp is (5-6):4, and the decomposition speed is (5000-8000) rpm.
[0011] Preferably, in S23, during the vacuum drying treatment, the temperature is (95-120)°C, the time is (15-20) min, and the vacuum degree is (0.096-0.098) MPa.
[0012] Preferably, in S3, the phenolic resin dispersion F is prepared by dissolving phenolic resin powder in ethanol, wherein the solid content of the phenolic resin powder is (1-1.5) wt %; During the impregnation, the carbon fiber paper E is completely immersed in the phenolic resin dispersion F for (5-10) min; When drying, the temperature is (95~110)℃ and the time is (1~1.5)h; During hot pressing, the temperature is (140~160)℃, the pressure is (9~10)MPa, and the time is (5~8)min.
[0013] Preferably, in S4, during the carbonization treatment, the protective gas is argon or nitrogen, the heating rate is (8-10)°C / min, the holding temperature is (700-1000)°C, and the holding time is (1-1.5)h.
[0014] A carbon fiber conductive base paper obtained by the preparation process of the resin cross-linked and shaped carbon fiber conductive base paper for hydrogen fuel cells has an air permeability of 7635-8251 mL / min and a square resistance of less than 5Ω / □.
[0015] A hydrogen fuel cell uses the carbon fiber conductive base paper as a gas diffusion layer.
[0016] Compared with the prior art, the present invention has the following beneficial effects: The invention discloses a process for preparing a resin cross-linked and shaped carbon fiber conductive base paper for hydrogen fuel cells. The process uses asphalt-based carbon fiber as a skeleton, aramid pulp as an auxiliary forming fiber, and low-concentration phenolic resin impregnation and high-temperature carbonization as strengthening means to prepare a carbon fiber conductive paper with high air permeability, thereby solving the contradiction between the conductivity and air permeability of the carbon fiber paper.
[0017] Compared with the publicly available process scheme, the raw material components are optimized first: on the one hand, aramid pulp fibers are introduced, and the good dispersion of aramid pulp after filamentization improves the uniformity of carbon fiber base paper and promotes fiber interweaving; on the other hand, low-concentration phenolic resin is used for impregnation and bonding to avoid pore blocking. In this structure, the introduced aramid pulp raw material is composed of alternating benzene rings and amide bonds, and the molecular structure has a high carbon content. The main molecular structure of the introduced phenolic resin is phenol and formaldehyde, and the molecular structure has a high carbon content. The carbon content is further increased after carbonization, forming a richer conductive network between the original fiber interweaving network, which is conducive to obtaining paper with higher conductivity and improving the comprehensive conductive properties of paper.
[0018] At the same time, the introduced aramid pulp, with its excellent flexibility and grip, can improve the flexibility and strength of the finished paper, effectively alleviate the brittleness and interface inertness of carbon fiber, and form a rich conductive network during the carbonization process, thereby significantly improving the comprehensive conductivity of the paper, successfully solving the contradiction between the strength, toughness and conductivity of carbon fiber. In addition, the ratio of aramid pulp is determined after long-term process optimization. If the content of aramid pulp is too low, the uniformity of the paper will not be significantly improved and the flexibility will be insufficient; if the content is too high, it will be unfavorable for the impregnation of the resin and easily block the pore structure of the paper.
[0019] Furthermore, the present invention, based on the introduction of aramid pulp as an auxiliary, realizes the bonding and strengthening of the interlacing points between carbon fibers, carbon fibers and aramid pulp, and aramid pulp by impregnation with ultra-low concentration phenolic resin. The relatively low concentration of phenolic resin can not only ensure the supplementation of insufficient fiber contact, facilitate the construction of the conductive network after subsequent carbonization, but also avoid clogging the pores of the paper, ensure its high air permeability, and realize the transmission of stress during the stretching process, improve the mechanical strength, and ensure the realization of paper performance.
[0020] Furthermore, the preferred aramid pulp terminal groups in the present invention contain rich amino groups, have good compatibility and self-binding ability with phenolic resin, and ensure high performance at low concentration. The principle is that the aramid pulp terminal groups can form extensive hydrogen bonds with the resin, and the curing of phenolic resin can cross-link the aramid pulp fiber filaments, so the two achieve high-strength bonding through the combined action of chemistry and physics.
[0021] Further, the present invention adds a process flow of high-temperature carbonization, because at the insufficient contact of the raw fiber, the phenolic resin that is infiltrated, bonded and solidified forms a tight network, and a richer conductive network can be constructed after high-temperature carbonization, thereby improving the comprehensive conductive properties of the carbon fiber paper. The heating rate is limited because the heating rate is too fast, and the O, N and other groups of the phenolic resin evaporate quickly, which will take away some C atoms, causing the residual carbon amount to decrease, which is not conducive to the construction of the conductive path. The insulation temperature is limited to ensure the conductive properties of the paper. Too high a temperature is not conducive to saving energy consumption. If the temperature is too low, the degree of carbonization is insufficient, and it is difficult to form a carbon element conductive network, and the conductive properties of the carbon fiber paper cannot be efficiently improved.
[0022] A carbon fiber conductive base paper of the present invention can be applied to the gas diffusion layer of a hydrogen fuel cell, and its main functions include charge collection, ventilation and water conduction. In terms of charge collection, it can efficiently transfer the electrons generated by the electrode reaction to the external circuit by virtue of good conductivity and low contact resistance, thereby reducing the internal resistance of the battery and improving the energy conversion efficiency of the battery. In terms of ventilation function, its porous structure provides an efficient transmission channel for the reaction gas, ensuring that hydrogen and oxygen can reach the catalyst layer evenly and quickly, and promoting the smooth progress of the electrochemical reaction. The water conduction function is to be able to discharge the water generated by the electrochemical reaction in time, prevent the occurrence of flooding, avoid hindering gas diffusion and electrode reaction, and ensure the stable operation of the battery. The combined effect of these functions helps to improve the performance and service life of the hydrogen fuel cell. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The present invention is a flow chart of a process for preparing a resin cross-linked and shaped carbon fiber conductive base paper for hydrogen fuel cells.
[0024] Figure 2 This is the surface SEM image of the carbon fiber base paper in Example 2.
[0025] Figure 3 This is the SEM image of the surface of the resin-impregnated carbon fiber paper in Example 3.
[0026] Figure 4 This is the SEM image of the surface of the carbonized carbon fiber conductive paper in Example 4. DETAILED DESCRIPTION
[0027] The present invention is further described in detail below in conjunction with specific embodiments, which are intended to explain the present invention rather than to limit it.
[0028] The present invention discloses a resin cross-linked carbon fiber conductive base paper for hydrogen fuel cells and a preparation process thereof. Figure 1 , including the following steps: S1, select aramid pulp with a length of 3-8 mm, a diameter of 7-8 μm, a resistivity of 1.5-2.0 μΩ·m, a tensile strength of 2.2-2.4 Gpa, and a breaking elongation of 0.25%-0.26%, add it into deionized water and soak it for 6-8 hours to obtain aramid pulp soaking liquid A. Among them, the conductivity of deionized water is (0.08-0.1) μS / cm, and the ratio of aramid pulp B to water is 1.0-1.2 g: 2L.
[0029] Then, 8 to 10 mL of a PEO dispersion having a concentration of 5 to 6 g / L is added to the aramid pulp soaking liquid A, and the mixture is deflated at 10,000 to 20,000 rpm using a fiber disintegrator to obtain a mixed system B.
[0030] S2, adding carbon fiber to the mixed system B for re-dispersion, and obtaining carbon fiber paper E through wet forming. Specifically: S21, select asphalt-based carbon fiber with a length of 7 mm, a diameter of 13 μm, a resistivity of 2.0 μΩ·m, a tensile strength of 2.3 Gpa, and an elongation at break of 0.25%, add the asphalt-based carbon fiber according to the absolute dry mass ratio of asphalt-based carbon fiber to aramid pulp of 5-6:4, add it to the aramid pulp suspension, disintegrate it at 5000-8000 rpm, and obtain a mixed fiber slurry C.
[0031] S22, pouring the mixed fiber slurry C into a paper sheet former to form a wet paper web D.
[0032] S23, the wet paper web D is vacuum dried to obtain carbon fiber paper E. Specifically, wool felt is spread on both sides to absorb moisture, and then vacuum dried in a paper sheet dryer at 95-120° C. for 15-20 minutes to obtain carbon fiber paper E.
[0033] S3, immersing the carbon fiber paper E in the phenolic resin dispersion F, and then drying and hot pressing to obtain the carbon fiber paper H.
[0034] Wherein, 5 g of phenolic resin powder was dissolved in 500-600 ml of anhydrous ethanol to obtain a phenolic resin dispersion F.
[0035] The carbon fiber paper E was immersed in the phenolic resin dispersion F for 5-10 minutes, and then placed in an oven and dried at 95-110°C for 1-1.5 hours to obtain the phenolic resin-impregnated carbon fiber paper G; the prepared resin-impregnated carbon fiber paper G was hot-pressed on a flat vulcanizer at 140-160°C and 9-10 MPa for 5-8 minutes to obtain the carbon fiber paper H.
[0036] S4, carbonizing the carbon fiber paper H under oxygen-isolating conditions to obtain carbon fiber conductive base paper. Specifically, the carbon fiber paper H is cut into small cubes with a side length of 2 to 5 cm, and argon or nitrogen is introduced into a tube furnace, and the heating rate is controlled to be 8 to 10°C / min, and the temperature is raised to 700 to 1000°C and kept for 1 to 1.5 hours to obtain the carbon fiber conductive paper.
[0037] The invention discloses a process for preparing a resin-crosslinked and shaped carbon fiber conductive base paper for hydrogen fuel cells. The process comprises soaking aramid pulp in deionized water, wet forming the mixed pulp, resin impregnation strengthening, hot pressing finishing and high-temperature carbonization to prepare a carbon fiber conductive paper with high air permeability. The process comprises auxiliary interweaving of aramid pulp, strengthening with low-concentration resin and high-temperature carbonization to solve the problem that it is difficult to achieve both high conductivity and high air permeability.
[0038] The deflaking machine, paper sheet former, dryer, hot press, tubular furnace, etc. used in the process scheme of the present invention are all conventional equipment, the solvents are tap water and ethanol, and the process links are environmentally friendly, which lays a good foundation for the industrialization and scale-up of the technology of the present invention and has a high market competitive advantage. The number of revolutions for pulp deflaking, the order of fiber addition, the drying temperature, the hot pressing finishing temperature, the hot pressing finishing pressure, and the insulation temperature of the carbonization process are all the results of process optimization. For example, the number of revolutions for pulp deflaking ensures that there is no breakage under high dispersion, the drying temperature ensures energy saving under high efficiency, the finishing temperature ensures no rheological blockage under phenolic resin curing, and the insulation temperature of the carbonization process ensures the construction of a conductive network. They are all the results of long-term process optimization, and the technical effect is to improve paper quality and save energy.
[0039] The invention also discloses a carbon fiber conductive paper obtained by resin cross-linked carbon fiber conductive base paper for hydrogen fuel cells and its preparation process. The carbon fiber conductive base paper has an air permeability of 7635-8251 mL / min and a square resistance of less than 5Ω / □.
[0040] The invention also discloses a hydrogen fuel cell, which uses carbon fiber conductive base paper as a gas diffusion layer.
[0041] Example 1 S1, shredding aramid pulp, soaking it in deionized water to obtain aramid pulp soaking liquid A, dispersing the soaking liquid, adding 10 mL of PEO dispersion liquid with a concentration of 5 g / L, and dispersing to obtain a mixed system B; S2, selecting asphalt-based carbon fiber with a length of 7 mm, a diameter of 13 μm, a resistivity of 2.0 μΩ·m, a tensile strength of 2.3 Gpa, and an elongation at break of 0.25%, adding asphalt-based carbon fiber according to the absolute dry mass ratio of asphalt-based carbon fiber to aramid pulp of 6:4, adding it to the aramid pulp suspension and dispersing it at 5000 rpm to obtain a mixed fiber slurry C; Pour the mixed fiber slurry C into a paper sheet former to obtain a wet paper web D; The wool felt was spread on both sides to absorb moisture, and then vacuum dried in a paper dryer at 120°C for 20 min to obtain carbon fiber paper E; S3, dissolving 5 g of phenolic resin powder in 600 ml of anhydrous ethanol to obtain a phenolic resin dispersion F; The prepared carbon fiber paper E was immersed in the phenolic resin dispersion F for 10 min, and then placed in an oven and dried at 105° C. for 1 h to obtain phenolic resin-impregnated carbon fiber paper G; The prepared resin-impregnated carbon fiber paper G was hot-pressed on a flat vulcanizer at 150° C. and 10 MPa for 5 min to obtain carbon fiber paper H.
[0042] S4, cut the carbon fiber paper H into small cubes with a side length of 3 cm, put them into a tubular furnace, pass argon protection, control the heating rate to 10°C / min, heat to 700°C and keep warm for 1h to obtain carbon fiber conductive paper.
[0043] The carbon fiber conductive paper prepared in this example has a basis weight of 90 g / m 2 , thickness is 0.156mm, air permeability reaches 7635 mL / min, square resistance is 15.19Ω / □, and it has high air permeability and high conductivity.
[0044] Example 2 S1, shredding aramid pulp, soaking it in deionized water to obtain aramid pulp soaking liquid A, dispersing the soaking liquid, adding 10 mL of PEO dispersion liquid with a concentration of 5 g / L, and dispersing to obtain a mixed system B; S2, selecting asphalt-based carbon fiber with a length of 7 mm, a diameter of 13 μm, a resistivity of 2.0 μΩ·m, a tensile strength of 2.3 Gpa, and an elongation at break of 0.25%, adding asphalt-based carbon fiber according to the absolute dry mass ratio of asphalt-based carbon fiber to aramid pulp of 6:4, adding it to the aramid pulp suspension and dispersing it at 5000 rpm to obtain a mixed fiber slurry C; Pour the mixed fiber slurry C into a paper sheet former to obtain a wet paper web D; The wool felt was spread on both sides to absorb moisture, and then vacuum dried in a paper dryer at 120°C for 20 min to obtain carbon fiber paper E; S3, dissolving 5 g of phenolic resin powder in 600 ml of anhydrous ethanol to obtain a phenolic resin dispersion F; The prepared carbon fiber paper E was immersed in the phenolic resin dispersion F for 10 min, and then placed in an oven and dried at 105° C. for 1 h to obtain phenolic resin-impregnated carbon fiber paper G; The prepared resin-impregnated carbon fiber paper G was hot-pressed on a flat vulcanizer at 150° C. and 10 MPa for 5 min to obtain carbon fiber paper H.
[0045] S4, cut the carbon fiber paper H into small cubes with a side length of 3 cm, put them into a tubular furnace, pass argon protection, control the heating rate to 10°C / min, heat to 800°C and keep warm for 1h to obtain carbon fiber conductive paper.
[0046] The carbon fiber conductive paper prepared in this example has a basis weight of 90 g / m 2 , with a thickness of 0.149mm, an air permeability of 8003mL / min, and a square resistance of 4.91Ω / □, which has high air permeability and high conductivity; Figure 2 , carbon fiber and aramid pulp are interwoven, and there are abundant pores.
[0047] Example 3 S1, shredding aramid pulp, soaking it in deionized water to obtain aramid pulp soaking liquid A, dispersing the soaking liquid, adding 10 mL of PEO dispersion liquid with a concentration of 5 g / L, and dispersing to obtain a mixed system B; S2, selecting asphalt-based carbon fiber with a length of 7 mm, a diameter of 13 μm, a resistivity of 2.0 μΩ·m, a tensile strength of 2.3 Gpa, and an elongation at break of 0.25%, adding asphalt-based carbon fiber according to the absolute dry mass ratio of asphalt-based carbon fiber to aramid pulp of 6:4, adding it to the aramid pulp suspension and dispersing it at 5000 rpm to obtain a mixed fiber slurry C; Pour the mixed fiber slurry C into a paper sheet former to obtain a wet paper web D; The wool felt was spread on both sides to absorb moisture, and then vacuum dried in a paper dryer at 120°C for 20 min to obtain carbon fiber paper E; S3, dissolving 5 g of phenolic resin powder in 600 ml of anhydrous ethanol to obtain a phenolic resin dispersion F; The prepared carbon fiber paper E was immersed in the phenolic resin dispersion F for 10 min, and then placed in an oven and dried at 105° C. for 1 h to obtain phenolic resin-impregnated carbon fiber paper G; The prepared resin-impregnated carbon fiber paper G was hot-pressed on a flat vulcanizer at 150° C. and 10 MPa for 5 min to obtain carbon fiber paper H.
[0048] S4, cut the carbon fiber paper H into small cubes with a side length of 3 cm, put them into a tubular furnace, pass argon protection, control the heating rate to 10°C / min, heat to 900°C and keep warm for 1h to obtain carbon fiber conductive paper.
[0049] The carbon fiber conductive paper prepared in this example has a basis weight of 90 g / m 2, with a thickness of 0.155mm, an air permeability of 8251 mL / min, and a square resistance of 3.11Ω / □, and has high air permeability and high conductivity. Figure 3 , carbon fiber and aramid pulp form an interwoven network with gas channels in the middle, which explains the reason for the high air permeability.
[0050] Example 4 S1, shredding aramid pulp, soaking it in deionized water to obtain aramid pulp soaking liquid A, dispersing the soaking liquid, adding 10 mL of PEO dispersion liquid with a concentration of 5 g / L, and dispersing to obtain a mixed system B; S2, selecting asphalt-based carbon fiber with a length of 7 mm, a diameter of 13 μm, a resistivity of 2.0 μΩ·m, a tensile strength of 2.3 Gpa, and an elongation at break of 0.25%, adding asphalt-based carbon fiber according to the absolute dry mass ratio of asphalt-based carbon fiber to aramid pulp of 6:4, adding it to the aramid pulp suspension and dispersing it at 5000 rpm to obtain a mixed fiber slurry C; Pour the mixed fiber slurry C into a paper sheet former to obtain a wet paper web D; The wool felt was spread on both sides to absorb moisture, and then vacuum dried in a paper dryer at 120°C for 20 min to obtain carbon fiber paper E; S3, dissolving 5 g of phenolic resin powder in 600 ml of anhydrous ethanol to obtain a phenolic resin dispersion F; The prepared carbon fiber paper E was immersed in the phenolic resin dispersion F for 10 min, and then placed in an oven and dried at 105° C. for 1 h to obtain phenolic resin-impregnated carbon fiber paper G; The prepared resin-impregnated carbon fiber paper G was hot-pressed on a flat vulcanizer at 150° C. and 10 MPa for 5 min to obtain carbon fiber paper H.
[0051] S4, cut the carbon fiber paper H into small cubes with a side length of 3 cm, put them into a tubular furnace, pass argon protection, control the heating rate to 10°C / min, heat to 1000°C and keep warm for 1h to obtain carbon fiber conductive paper.
[0052] The carbon fiber conductive paper prepared in this example has a basis weight of 90 g / m 2 , with a thickness of 0.151mm, an air permeability of 7856 mL / min, and a square resistance of 2.38Ω / □, which has high air permeability and high conductivity. Figure 4 After carbonization, the phenolic resin forms a richer conductive network between the original fiber interlaced network, making the conductive path richer and the conductivity higher, which explains why the prepared carbon fiber conductive paper has a small square resistance.
[0053] Example 5 S1, shredding aramid pulp, soaking it in deionized water to obtain aramid pulp soaking liquid A, dispersing the soaking liquid, adding 10 mL of PEO dispersion liquid with a concentration of 5 g / L, and dispersing to obtain a mixed system B; S2, selecting asphalt-based carbon fiber with a length of 7 mm, a diameter of 13 μm, a resistivity of 2.0 μΩ·m, a tensile strength of 2.3 Gpa, and an elongation at break of 0.25%, adding asphalt-based carbon fiber according to the absolute dry mass ratio of asphalt-based carbon fiber to aramid pulp of 6:4, adding it to the aramid pulp suspension and dispersing it at 5000 rpm to obtain a mixed fiber slurry C; Pour the mixed fiber slurry C into a paper sheet former to obtain a wet paper web D; The wool felt was spread on both sides to absorb moisture, and then vacuum dried in a paper dryer at 120°C for 20 min to obtain carbon fiber paper E; S3, dissolving 5 g of phenolic resin powder in 600 ml of anhydrous ethanol to obtain a phenolic resin dispersion F; The prepared carbon fiber paper E was immersed in the phenolic resin dispersion F for 10 min, and then placed in an oven and dried at 105° C. for 1 h to obtain phenolic resin-impregnated carbon fiber paper G; The prepared resin-impregnated carbon fiber paper G was hot-pressed on a flat vulcanizer at 150° C. and 10 MPa for 5 min to obtain carbon fiber paper H.
[0054] S4, cut the carbon fiber paper H into small cubes with a side length of 3 cm, put them into a tubular furnace, pass argon protection, control the heating rate to 10°C / min, heat to 1100°C and keep warm for 1h to obtain carbon fiber conductive paper.
[0055] The carbon fiber conductive paper prepared in this example has a basis weight of 90 g / m 2 , thickness is 0.153mm, air permeability reaches 8159 mL / min, square resistance is 1.86Ω / □, and it has high air permeability and high conductivity.
[0056] Table 1 Technical parameters of carbon fiber base paper prepared in Examples 1 to 4
[0057] Table 1 shows the technical parameters of the carbon fiber base paper prepared in the examples. From the data analysis, it can be obtained that the carbon fiber base paper prepared by the process provided by the present invention has an air permeability of 7635-8251 mL / min, which is a relatively high level. This is because the asphalt-based carbon fiber and aramid pulp are fully interwoven, but the high porosity is retained. The square resistance of the carbon fiber conductive paper obtained by carbonization in Examples 2 to 5 is less than 5Ω / □, achieving a relatively high conductivity. This is because the high temperature carbonizes the aramid pulp and phenolic resin, forming a rich conductive network on the basis of the base paper, thereby enhancing the conductive performance of the carbon fiber paper.
[0058] The above description is only a preferred embodiment of the present invention and is not intended to impose any limitation on the technical solution of the present invention. Those skilled in the art should understand that, without departing from the spirit and principles of the present invention, the technical solution can also be subjected to several simple modifications and substitutions, and these modifications and substitutions are also within the scope of protection covered by the claims.
Claims
1. A process for preparing resin cross-linked carbon fiber conductive base paper for hydrogen fuel cells, characterized in that: The following steps are involved: S1, shredding aramid pulp and soaking it in deionized water to obtain aramid pulp soaking liquid A, then adding PEO dispersant to obtain a mixed system B; S2, adding carbon fiber to the mixed system B for re-dispersion, and obtaining carbon fiber paper E through wet forming; S3, immersing the carbon fiber paper E in the phenolic resin dispersion F, and then drying and hot pressing to obtain the carbon fiber paper H; S4, carbonizing the carbon fiber paper H under oxygen-isolating conditions to obtain a carbon fiber conductive base paper.
2. The process for preparing a resin cross-linked and shaped carbon fiber conductive base paper for hydrogen fuel cells according to claim 1, characterized in that: The relevant requirements for aramid pulp are as follows: length 3-8 mm, diameter 7-8 μm, resistivity 1.5-2.0 μΩ·m, tensile strength 2.2-2.4 Gpa, elongation at break 0.25%-0.26%; The concentration of the PEO dispersion is 5-6 g / L; the conductivity of the deionized water is (0.08-0.1) μS / cm.
3. The process for preparing a resin cross-linked carbon fiber conductive base paper for hydrogen fuel cells according to claim 1, characterized in that: In S1, the ratio of aramid pulp B to water is 1.0-1.2 g: 2 L, and the soaking time of aramid pulp is more than (6-8) h; The amount of the PEO dispersant used is (1.5-2.0) wt% of the total absolute dry mass of the carbon fiber and aramid pulp, and the number of revolutions during disintegration is (10000-20000) rpm.
4. The process for preparing a resin cross-linked and shaped carbon fiber conductive base paper for hydrogen fuel cells according to claim 1, characterized in that: The preparation method of carbon fiber paper E is as follows: S21, adding asphalt-based carbon fiber to the mixed system B, mixing evenly and dispersing again to obtain a mixed fiber slurry C; S22, homogenizing and dehydrating the mixed fiber slurry C to obtain a wet paper web D; S23, the wet paper web D is subjected to vacuum drying to obtain carbon fiber paper E.
5. The process for preparing a resin cross-linked and shaped carbon fiber conductive base paper for hydrogen fuel cells according to claim 4, characterized in that: In S21, the absolute dry mass ratio of the added asphalt-based carbon fiber to the aramid pulp is (5-6):4, and the decomposition speed is (5000-8000) rpm.
6. The process for preparing a resin cross-linked and shaped carbon fiber conductive base paper for hydrogen fuel cells according to claim 4, characterized in that: In S23, during the vacuum drying process, the temperature is (95-120)°C, the time is (15-20) min, and the vacuum degree is (0.096-0.098) MPa.
7. The process for preparing a resin cross-linked carbon fiber conductive base paper for hydrogen fuel cells according to claim 1, characterized in that: In S3, a phenolic resin dispersion F is prepared by dissolving phenolic resin powder in ethanol, wherein the solid content of the phenolic resin powder is (1-1.5) wt %; During the impregnation, the carbon fiber paper E is completely immersed in the phenolic resin dispersion F for (5-10) min; When drying, the temperature is (95~110)℃ and the time is (1~1.5)h; During hot pressing, the temperature is (140~160)℃, the pressure is (9~10)MPa, and the time is (5~8)min.
8. The process for preparing a resin cross-linked and shaped carbon fiber conductive base paper for hydrogen fuel cells according to claim 1, characterized in that: In S4, during the carbonization treatment, the protective gas is argon or nitrogen, the heating rate is (8~10)℃ / min, the holding temperature is (700~1000)℃, and the holding time is (1~1.5)h.
9. A carbon fiber conductive base paper obtained by the process for preparing the resin cross-linked and shaped carbon fiber conductive base paper for hydrogen fuel cells according to any one of claims 1 to 9, characterized in that: The air permeability of the carbon fiber conductive base paper is 7635-8251 mL / min, and the square resistance is less than 5Ω / □.
10. A hydrogen fuel cell, characterized in that: The hydrogen fuel cell uses the carbon fiber conductive base paper described in claim 9 as a gas diffusion layer.
Citation Information
Patent Citations
Industrial high-temperature carbon fiber electric heating paper and making method thereof
CN102465475A
A method for preparing carbon fiber paper for fuel cell gas diffusion layer
CN119121695B
Carbon fiber paper construction & manufacturing process
US20060214320A1
Porous carbon electrode substrate, method of manufacturing same, gas diffusion layer, and membrane-electrode assembly for fuel cell
US20180069245A1
Preparation method of carbon fiber paper
CN113584940A